Ethno-Biology Learning Model Based on Design Thinking to Improve Students' Critical Thinking Skills - Linda Winiasri; Tomi Apra Santosa; Yohandri Yohandri; Abdul Razak; Festiyed Festiyed; Zulyusri Zulyusri (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to investigate the effect of an ethnobiology learning model based on design thinking on students' critical thinking skills. The research is a type of quasi-experimental research with a randomized control group pretest-postest design. The population of this study came from SMA Negeri 12 Kerinci. The research sample came from two classes, namely class XI MIPA (experimental class) and class MIPA 3 (control class) totaling 42 students. The experimental class group used the ethnobiology learning model while the control class group used the conventional learning model. The sampling technique is random sampling. The research instrument was an objective test of critical thinking skills. Data analysis was quantitative statistical analysis with the help of SPSS version 26. The results of this study showed that the average value of posttest and N-gain critical thinking skills of classes that obtained ethnobiology learning based on design thinking was better than classes that used conventional learning. The t-test results show that the ethnobiology learning model based on design thinking has an effect on critical thinking skills sig. < 0.05 (0.00 < 0.05). Students' thinking skills in the experimental class obtained an average score of 82.30 with an N-gain value of 0.72